Mitochondria and Inflammation: Cell Death Heats Up - Vringer, Esmee; Tait, Stephen W. G. (Frontiers in Cell and Developmental Biology, 2019)
Mitochondrial outer membrane permeabilization (MOMP) is essential to initiate mitochondrial apoptosis. Due to the disruption of mitochondrial outer membrane integrity, intermembrane space proteins, notably cytochrome c, are released into the cytosol whereupon they activate caspase proteases and apoptosis. Nevertheless, beyond its well-established apoptotic role, MOMP has recently been shown to display potent pro-inflammatory effects. These include mitochondrial DNA dependent activation of cGAS-STING signaling leading to a type I interferon response. Secondly, via an IAP-regulated mechanism, MOMP can engage pro-inflammatory NF-B signaling. During cell death, apoptotic caspase activity inhibits mitochondrial dependent inflammation. Importantly, by engaging an immunogenic form of cell death, inhibiting caspase function can effectively inhibit tumorigenesis. Unexpectedly, these studies reveal mitochondria as inflammatory signaling hubs during cell death and demonstrate its potential for therapeutic exploitation.